A toxicokinetic and toxicodynamic modeling approach using Myriophyllum spicatum to predict effects caused by short‐term exposure to a sulfonylurea. (15th December 2015) - Heine, Simon; Schild, Frederik; Schmitt, Walter; Krebber, Ralph; Görlitz, Gerhard; Preuss, Thomas G.
Abstract: Toxicokinetic and toxicodynamic models are a promising tool to address the effects of time‐variable chemical exposure. Standard toxicity tests usually rely on static concentrations, but these chemical exposure patterns are unlikely to appear in the field, where time‐variable exposure of chemicals is typical. In the present study, toxicodynamic processes were integrated into an existing model that includes the toxicokinetics and growth of the aquatic plant Myriophyllum spicatum, to predict the impact on plant growth of 2 iofensulfuron short‐term exposure patterns. To establish a method that can be used with standard data from risk assessments, the toxicodynamics of iofensulfuron were based on effect data from a 14‐d standard toxicity test using static concentrations. Modeling showed that the toxicokinetic and toxicodynamic growth model of M. spicatum can be successfully used to predict effects of short‐term iofensulfuron exposure by using effect data from a standard toxicity test. A general approach is presented, in which time‐variable chemical exposures can be evaluated more realistically without conducting additional toxicity studies. Environ Toxicol Chem 2016;35:376–384. © 2015 SETAC